Long-term follow-up results of ruxolitinib as salvage therapy for chronic graft-versus-host disease - Neslihan Mandaci Sanli; Esen Karakuş (Hematology, Transfusion and Cell Therapy)
Introduction: Chronic graft-versus-host disease poses a significant challenge after allogeneic hematopoietic stem cell transplantation with initial treatment often relying on high-dose steroids. However, managing steroid-refractory disease remains daunting. Recent insights into the mechanisms have unveiled new treatment targets, with ruxolitinib, a selective JAK1/2 inhibitor, emerging as a promising and safe therapy for chronic graft-versus-host disease patients. Methods: This retrospective study describes the long-term outcomes of 23 chronic graft-versus-host disease patients treated with ruxolitinib. Results: Most patients presented with severe chronic graft-versus-host disease (15/23; 65.2%). The overall response rate was 78.3% (18/23) after a median treatment duration of four weeks, with 55.6% (10/18) achieving complete response. At follow-up, 13 of the 18 responders (72.2%) sustained complete remission. Patients had a median of two previous lines of therapy, with a median follow-up of 14 months (range: 2–46 months) after starting ruxolitinib. Of the patients who were responsive to ruxolitinib, median follow-up extended to 26.5 months. Notably, for the patients who were responsive to ruxolitinib, the 1-year, 2-year, and 3-year overall survival was 83.3% (95% CI: 64.2%-102%), 56.1% (95% CI: 30.1%-80.9%), and 33.3% (95% CI: 9.2%-57.4%), respectively. Malignancy relapse occurred in 17.4% (4/23) of patients, with 34.7% (8/23) experiencing cytopenias, albeit mostly mild. Reactivation rates for cytomegalovirus were nil. Conclusion: The long-term follow-up in this study supports ruxolitinib as an effective salvage therapy for chronic graft-versus-host disease with a 78.3% overall response rate and 55.6% complete remission rate. However, large prospective studies are warranted to validate these findings